TINGKAT PENGETAHUAN PASIEN TENTANG EFEK SAMPING OBAT CAPTOPRIL DAN AMLODIPIN DI PUSKESMAS SUNGAI JINGAH - Novia Ariani; Dwi Rizki Febrianti; Rakhmadhan Niah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Hypertension is an increase in systolic and diastolic blood pressure of more than 140 mmHg and90 mmHg. Captopril and Amlodipin are the most commonly used antihypertensive drugs, especially in Sungai Jingah Health Center. Long-term use is most likely to cause side effects. The level of knowledge of patients about side effects is very influential in knowing the early signs of the emergence of side effects and can prevent complications caused by side effects. The purpose of this study was to determine the level of patient knowledge about the side effects of captopril and amlodipine drugs at Sungai Jingah Health Center. This research is a non-experimental observational study. The population used was all hypertensive patients who received captopril and amlodipine drugs at the Sungai Jingah Health Center in April-May 2019. Samples were taken with consecutive sampling techniques that met the inclusion criteria of 55 patients. The research instrument used a questionnaire sheet that had been tested for validity and reliability consisting of 4 statements about the side effects of captopril and 5 items about the side effects of amlodipine. The data obtained is recapitulated and calculated using the percentage formula for each statement then presented descriptively. The results of the research on the level of knowledge about the side effects of captopril and amlodipine showed that out of 55 respondents 80.00% had a low level of knowledge, 3.64% had sufficient knowledge and 16.36% had good knowledge. The conclusion of this study is that the level of knowledge of patient knowledge about the side effects of captopril and amlodipine is in the low category (80.00%).